Predictive Performance of Gram Staining of Catheter Tips for Candida Catheter-Related Bloodstream Infections. (12th December 2022) - Yamada, Gen; Iwamoto, Noriko; Ishikane, Masahiro; Moriya, Ataru; Kurokawa, Masami; Mezaki, Kazuhisa; Ohmagari, Norio
Abstract: We analyzed 2462 episodes of suspected catheter-related bloodstream infection (CRBSI). The sensitivity, specificity, and positive and negative predictive values for detecting Candida CRBSI by gram staining of catheter tips were 66.1%, 99.4%, 84.4%, and 98.4%, respectively. Gram staining may be useful for the early detection of Candida CRBSI. Abstract : We analyzed 2462 episodes of suspected catheter-related bloodstream infection (CRBSI). The positive predictive value for detecting Candida CRBSI by Gram staining of catheter tips was 84.4%. Gram staining may be useful for the early detection of Candida CRBSI.